2015
DOI: 10.1002/etc.2970
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the causes of sediment‐associated toxicity in urban waterways in South China: Incorporating bioavailabillity‐based measurements into whole‐sediment toxicity identification evaluation

Abstract: Sediments in urban waterways of Guangzhou, China, were contaminated by a variety of chemicals and showed prevalent toxicity to benthic organisms. A combination of whole-sediment toxicity identification evaluation (TIE) and bioavailability-based extraction was used to identify the causes of sediment toxicity. Of the 6 sediment samples collected, 4 caused 100% mortality to Chironomus dilutus in 10-d bioassays, and the potential toxicants were assessed using TIE in these sediments after dilution. The results of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 38 publications
2
39
1
Order By: Relevance
“…The TIE approach is divided into three phases: characterization into main classes with physical and chemical manipulations (Phase I), identification of the toxicants through analytical techniques and a toxicity evaluation (Phase II), and confirmation of the actual causes of toxicity through collating the corroborating toxicant data (Phase III) 10, 12 . This method has been used successfully for identifying toxicants in both sediment interstitial water and pure sediment 11, 13, 14 . Previous studies have shown that better outcomes are expected from a TIE of aggregated sediment than from observations of intact sediments in situ 10, 15, 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TIE approach is divided into three phases: characterization into main classes with physical and chemical manipulations (Phase I), identification of the toxicants through analytical techniques and a toxicity evaluation (Phase II), and confirmation of the actual causes of toxicity through collating the corroborating toxicant data (Phase III) 10, 12 . This method has been used successfully for identifying toxicants in both sediment interstitial water and pure sediment 11, 13, 14 . Previous studies have shown that better outcomes are expected from a TIE of aggregated sediment than from observations of intact sediments in situ 10, 15, 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The TIE procedure has been routinely used for environmental risk assessments in North America, Europe, Australia and Brazil 8, 1719 , where the level of contamination was relatively low and the toxicity in sediment was mainly identified as arising from a single class of contaminants 13, 20 . In China, however, few studies have applied the TIE approach to identify contaminants in sediments 12, 13, 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their persistence, bioaccumulation and toxicity, these contaminants posed potential risk to aquatic organisms. Yi et al (2015) reported that the sediments from urban waterways in South China were seriously deteriorated by a suite of contaminants and caused high lethality to the benthic invertebrate, Chironomus dilutus. Whole sediment toxicity identification evaluation testing found that the toxicity was caused jointly by current-use insecticides (cypermethrin, lambda-cyhalothrin and fipronil) and metals (Zn, Ni and Pb) (Yi et al, 2015), indicating the need to understand the interaction between these contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Phase II measures target toxicants using different analytical techniques, while Phase III confirms, or otherwise, that the suspect toxicants identified in Phases I and II of the TIE procedures are actually causing the observed toxicity. Indeed, TIE procedures have been employed to identify toxic components in water and sediments in water bodies in China (e.g., Ke et al, 2015;Yi et al, 2015). Over and above this, effect-directed analysis procedures are currently being developed to deal with issues arising from mixtures of pollutants in the management of water resources ( .…”
mentioning
confidence: 99%